[tex]\displaystyle\\
\bf\\
\text{folosim formulele:}\\
\cos (a+b) = \cos a \cdot \cos b - \sin a \cdot \sin b \\
\cos (a-b) = \cos a \cdot \cos b + \sin a \cdot \sin b \\\\
\text{Rezolvare:}\\\\\\
\frac{\cos(a+b)+\sin a \cdot \sin b}{cos(a-b)-\sin a\cdot \sin b} =\\\\\\
=\frac{ \cos a \cdot \cos b \overbrace{- \sin a \cdot \sin b+\sin a \cdot \sin b}^{=0}}{\cos a \cdot \cos b + \underbrace{\sin a \cdot \sin b-\sin a\cdot \sin b}_{=0}} = \frac{ \cos a \cdot \cos b}{ \cos a \cdot \cos b}=\boxed{1}[/tex]